2006
DOI: 10.1073/pnas.0508103103
|View full text |Cite
|
Sign up to set email alerts
|

A SNP in the flt-1 promoter integrates the VEGF system into the p53 transcriptional network

Abstract: The VEGF system is essential for angiogenesis. VEGF overexpression frequently correlates with increased microvascularity and metastasis and decreased spontaneous apoptosis. Although a precise mechanism has not been established, studies suggest that VEGF expression is negatively regulated by p53, a master regulator and tumor suppressor. There are no reports of additional components of the VEGF signal transduction pathway being part of the p53 transcriptional network. A target of VEGF, the VEGF receptor 1͞flt-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 41 publications
4
70
0
Order By: Relevance
“…Fitting with this hypothesis, it has been previously reported a transcriptional cooperation between p53 and a ligand-bound estrogen receptor to result in a regulatory cross talk synergistically transactivating VEGFR1/FLT1, whereas p53 alone has relatively no effect. 29,30 In addition, Pax6-downregulated FOXM1 and MCM5 genes were not affected by p53 RNA interference despite it has been reported in other cell systems that p53 could also repress their expression independently of Pax6 signaling. 31,32 Thus, cross talk between Pax6 signaling and p53 activity appears to regulate specific genes in a given environment as the identification of either Pax6 or p53 target genes greatly varies depending on the cell system used.…”
Section: Discussionmentioning
confidence: 80%
“…Fitting with this hypothesis, it has been previously reported a transcriptional cooperation between p53 and a ligand-bound estrogen receptor to result in a regulatory cross talk synergistically transactivating VEGFR1/FLT1, whereas p53 alone has relatively no effect. 29,30 In addition, Pax6-downregulated FOXM1 and MCM5 genes were not affected by p53 RNA interference despite it has been reported in other cell systems that p53 could also repress their expression independently of Pax6 signaling. 31,32 Thus, cross talk between Pax6 signaling and p53 activity appears to regulate specific genes in a given environment as the identification of either Pax6 or p53 target genes greatly varies depending on the cell system used.…”
Section: Discussionmentioning
confidence: 80%
“…Bioinformatic search for the p53 consensus sequence (el-Deiry et al, 1992) revealed two motifs, in the hPar1 promoter residing between À2936 to À2916 and À1704 to À1724, upstream to the PAR1 coding region. Although the first site matches the traditional p53-binding consensus motif with one mismatch, the second site matches only half of the p53-binding consensus motif (Weinberg et al, 2005;Menendez et al, 2006). (H1299 p53/371C).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, slot blot, Southern blot and cloning and sequencing were used. More recently, immunoprecipitated DNA is PCR amplified and viewed on a gel or with quantitative real-time monitoring [81,82]. Additionally, immunoprecipitated DNA can be measured genome-wide by hybridizing to a genomic tiling microarray, procedurally known as ChIP-on-chip or ChIP-chip [83].…”
Section: Chromatin Immunoprecipitation-a Concern Withmentioning
confidence: 99%